Analisis Beban Kerja dan Keseimbangan Kehidupan Kerja Terhadap Kesehatan Mental Karyaawan Pada Hotel Fairfield by Marriott Bali Legian - Made Rosmita Cintya Dewi; I Putu Yoga Laksana; Muhammad Panji Mahardika (CV. ITTC INDONESIA, 2026)
The hospitality industry operates within an inherently dynamic ecosystem, often subjecting the workforce to intense physical and psychological strain to maintain service excellence. Grounded in the Job Demands-Resources Theory, job demands can impair mental well-being, while job resources act as a protective buffer. This study aims to analyze the causal impacts of workload intensity and work-life balance on the mental health of employees at Fairfield by Marriott Bali Legian. This quantitative research involved a population of 189 operational and administrative personnel. A total of 127 respondents were selected using proportionate stratified random sampling. Data were collected via validated questionnaires and analyzed using multiple linear regression with SPSS software. The empirical results indicate that excessive workload exerts a significant negative effect on employee mental health. Conversely, a supportive work-life balance paradigm projects a substantial positive influence. Simultaneously, both variables account for 73.1% of the statistical variance in mental health outcomes. The discourse unequivocally advocates for organizational leadership to dynamically re-engineer workload distributions and nurture a culture that champions work-life equilibrium to safeguard the workforce's cognitive longevity and operational resilience.